Presenting a Model of the Impact of Elderly Exercise and Health-Oriented Lifestyle on Life Expectancy of the Elderly with the Mediating Role of Social Marketing - Mozafari, Bagher; Abdavi, Fatemeh; Khodadadi, Mohammad Rasol (Health Nexus, 2024)
The aim of this study is to present a model of the impact of elderly exercise and health-oriented lifestyle on life expectancy of the elderly, with the mediating role of social marketing. The research method is qualitative and based on the thematic analysis approach. Based on qualitative research, the participants in this study included academic elites and experts in the field of elderly exercise. The sample selection in the qualitative section was done theoretically and in a judgmental manner. The estimated sample size was based on the theoretical saturation of the extracted components of the research. The measurement tool was an open interview, and the findings were analyzed using MAXQDA software. Based on the findings, the components of the position of elderly exercise include cultural position, sports support, sports infrastructure, sports security, and social position. The components of life expectancy of the elderly include creative decision-making, goal-setting, spirituality, and constructive communication. The components of a health-oriented lifestyle for the elderly include personal health, mental health, social health, and functional health. The components of social marketing in elderly exercise include access to facilities, media role, participatory engagement, planning, and education. Therefore, it is suggested that in order to achieve the strategic goals of elderly exercise, attention should be paid to a health-oriented lifestyle and social marketing in elderly sports to achieve a hopeful society.